PERANCANGAN PLTS ATAP DI GEDUNG GRAHA SEWAKA DHARMA - I Gede Agus Januar Ariawan; Ida Ayu Dwi Giriantari; I Wayan Sukerayasa (Program Studi Teknik Elektro UNUD, 2021)
The utilization of renewable energy can be a solution to support the supply of electricalenergy, one of which is the use of solar energy with rooftop solar panels. In this study, the roofof the Graha Sewaka Dharma Building was used as a location for the design of rooftop solarpower plants to be able to help with electrical energy needs and support government programsin developing the use of solar energy. The total roof area of Graha Sewaka Dharma Building is1,616.37 m2. This design uses a battery-free On-grid PLTS system using a Solaria PowerXT-400R-PM solar module with a capacity of 400 Wp and a Ginlong Solis S5-GC36K-LV inverterwith a capacity of 36 kW. This design will calculate the capacity of solar modules that can beinstalled and the electrical energy produced with the limitation of the roof area and load profile inthe Graha Sewaka Dharma Building. Based on the results of the study, the capacity of therooftop PLTS installed in the Graha Sewaka Dharma Building is 188.8 kWp with a total of 472solar module units and 6 inverter units. The energy output produced per year (energy yield) is306,2 MWh/year. The investment feasibility study using the methods Net Present Value,Profitability Index, and Discounted Payback Period shows that this design investment isfeasible. Further research is recommended to study the impact of reducing carbon emissions onthe use of the PV grid.